The ‘Continuous City’ versus the ‘Ruptured City’. Review of Daniel Solomon’s book, Housing and the City: Love versus Hope (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2020)
Daniel Solomon’s Housing and the City: Love versus Hope examines why Modern architects and planners across the globe have produced so many badly connected cities and neighborhoods. Modernist cities suffer from too many self-contained buildings and projects and lifeless outdoor spaces. Rejection of traditional urbanism led to a fractured modernist cityscape in which walking is unpleasant or unproductive. Reviewer Philip Langdon says a New York Museum of Modern Art exhibition of city planning in post-World War II Yugoslavia unintentionally confirmed the validity of Solomon’s argument. Solomon asserted that instead of building isolating, automobile-dependent “Ruptured Cities,” we should create “Continuous Cities”: places that mix a variety of people and that blend together buildings from past and present. Properly designed streets, squares, courtyards, and other open spaces help residents enjoy and learn from urban life. He presents examples of destructive urban development in Brasilia, Paris, and other cities, and discusses uplifting examples from Rome, Stockholm, Amsterdam, San Francisco, and elsewhere. The HOPE VI program in the U.S. is shown to be successful at redeveloping failed public housing projects.